2017
DOI: 10.1007/s11096-017-0571-y
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems identified during geriatric medication review in the community pharmacy

Abstract: Background In line with the changing role of community pharmacists, we describe here a standardised procedure for detecting DRPs in elderly patients for use in community pharmacies. Objectives The primary aim was to describe the number and type of DRPs identified by community pharmacists in elderly patients. Secondary aims were to determine the number and type of associated pharmacist interventions (PIs) that were transmitted to the prescribers, and to identify risk factors associated with the occurrence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 29 publications
2
36
5
Order By: Relevance
“…In previous studies, the average number of DRPs per person was lower than the result in our study. 15,16 There might be several explanations for why the number of DRPs in this study was higher than in other studies. First, our study was conducted in a tertiary hospital rather than a community pharmacy.…”
Section: Discussioncontrasting
confidence: 61%
“…In previous studies, the average number of DRPs per person was lower than the result in our study. 15,16 There might be several explanations for why the number of DRPs in this study was higher than in other studies. First, our study was conducted in a tertiary hospital rather than a community pharmacy.…”
Section: Discussioncontrasting
confidence: 61%
“…Among the included studies, eight were conducted in Europe, 14e20,24 two in Australia, 12,21 two in North America, 22,23 and one in Asia. 13 Regarding the study design, three studies were retrospective, 12,19,21 three studies were prospective, 13,16,20 four studies were randomized controlled trials, 15,17,22,23 and two studies were crosssectional. 14,18 The included studies identified DRPs during the MR process; according to the "PCNE statement on medication review 2013," 25 four studies performed a PCNE type 1/basic MR, 12,17,21,24 two studies performed a PCNE type 2b/intermediate MR, 14,20 and six studies performed a PCNE type 3/ advanced MR. 13,15,16,18,22 Three studies analyzed the impact of patients' participation in the improvement of the MR process.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The simplified 100% review of MO by clinical pharmacists, prior to drug dispensing, is one of the main strategies for DRP prevention in patients followed at various levels of healthcare, [36][37][38] especially in a hospital environment, where the risk of DRP is related to several factors such as polypharmacy, comorbidities, use of high-risk medication, renal/hepatic insufficiency, clinical condition, prolonged hospitalisation, among others. 23 39 This is a very common reality in most health services.…”
Section: Open Accessmentioning
confidence: 99%